Determination of cytochrome P-448 activity in biological tissues. - Phillipson, C E (1984)
Three enzymes used for the determination of cytochrome P-448 activity, namely aryl hydrocarbon hydroxylase, biphenyl 2-hydroxylase and ethoxyresorufin O-de-ethylase, were evaluated with respect to their specificity, sensitivity and inducibility. Purified cytochrome P-448 (LM4), but not cytochrome P-450 (LM2), catalysed the O-de-ethylation of ethoxyresorufin in a reaction that was markedly inhibited by 9-hydroxyellipticine. After the administration of 3-methylcholanthrene to rats all three activities were induced, the extent of induction being highest for ethoxyresorufin O-de-ethylase. Administration of very small doses of benzo[a]pyrene (50 micrograms/kg) to rats to induce cytochrome P-448 specifically increased only the O-de-ethylation of ethoxyresorufin. 3-Hydroxybenzo[a]pyrene, the major metabolite determined by the aryl hydrocarbon hydroxylase assay, undergoes further NADPH-dependent oxygenation leading to loss of fluorescence. On the basis of these observations and those by other workers, we conclude that ethoxyresorufin O-de-ethylase provides the most specific, sensitive and reproducible means of determining cytochrome P-448 activity.